Diabetes Management in Chronic Kidney Disease: Synopsis of the KDIGO 2022 Clinical Practice Guideline Update - Navaneethan, Sankar D; Zoungas, Sophia; Caramori, M Luiza; Chan, Juliana C N; Heerspink, Hiddo J L; Hurst, Clint; Liew, Adrian; Michos, Erin D; Olowu, Wasiu A; Sadusky, Tami; Tandon, Nikhil; Tuttle, Katherine R; et al. (Annals of internal medicine, 2023)
The KDIGO 2022 Clinical Practice Guideline for Diabetes Management in Chronic Kidney Disease is an update of the 2020 guideline from Kidney Disease: Improving Global Outcomes (KDIGO). The KDIGO Work Group updated the guideline, which included reviewing and grading new evidence that was identified and summarized. As in the previous guideline, the Work Group used the GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach to appraise evidence and rate the strength of recommendations and expert judgment to develop consensus practice points. New evidence led to updating of recommendations in the chapters Comprehensive Care in Patients With Diabetes and CKD (Chapter 1) and Glucose-Lowering Therapies in Patients With T2D and CKD (Chapter 4). New evidence did not change recommendations in the chapters Glycemic Monitoring and Targets in Patients With Diabetes and CKD (Chapter 2), Lifestyle Interventions in Patients With Diabetes and CKD (Chapter 3), and Approaches to Management of Patients With Diabetes and CKD (Chapter 5). The updated guideline includes 13 recommendations and 52 practice points for clinicians caring for patients with diabetes and chronic kidney disease (CKD). A focus on preserving kidney function and maintaining well-being is recommended using a layered approach to care, starting with a foundation of lifestyle interventions, self-management, and first-line pharmacotherapy (such as sodium-glucose cotransporter-2 inhibitors) demonstrated to improve clinical outcomes. To this are added additional drugs with heart and kidney protection, such as glucagon-like peptide-1 receptor agonists and nonsteroidal mineralocorticoid receptor antagonists, and interventions to control risk factors for CKD progression and cardiovascular events, such as blood pressure, glycemia, and lipids.